Novel peer review method for improving controlled substance prescribing in primary care - Penti, MD, MS, Brian; Liebschutz, MD, MPH, FACP, Jane M.; Kopcza, PharmD, BCACP, Brian; Xuan, ScD, Ziming; Odell, MD, MSc, Christine; Saper, MD, MPH, Robert (Journal of Opioid Management, 2016)
Objective: Determine if peer feedback through a chart review tool (CRT) can impact opioid prescribing for patients with chronic noncancer pain in an outpatient family medicine clinic at an urban, safety-net teaching hospital and to assess providing practices. Design: A quality improvement (QI) project, comparing preopioid and postopioid prescribing practices. Setting: Outpatient family medicine clinic at urban, safety-net teaching hospital. Patients, Participants: A convenience sample of 16 family medicine physicians. Interventions: A CRT was developed to allow physicians to give peer feedback to one another about their opioid prescribing practices as part of a 1-year QI project. We assessed the deidentified data gathered from the CRT. Main Outcome Measure(s): Primary study outcome measures were the amount of opioids prescribed at the end of the QI project compared to the time of initial chart review. We also describe overall prescribing practices. Results: Ninety-nine patient charts from 14 different physicians were reviewed over 1 year. Sixty percent of patients had at least one violation of the clinic’s controlled substance prescribing policy in the prior 6 months, and half of the violations were due to missed appointments with specialists to help manage pain. The mean dose of opioids decreased 2.6 mg morphine equivalent dose (MED)/day from time of chart review until the end of project, compared to a 6.9 mg MED/day increase that occurred from 12 months prior to chart review to the time of chart review (p = 0.01). Fourteen patients (16 percent) of patients prescribed opioids were takenoff of opioids after the chart review. Conclusions: Use of a CRT in an urban primary care clinic provided helpful insight on prescribing practices and has promise to improve quality of opioid prescribing.